Landholding size and farmers' access to credit and its utilisation in Pakistan. Issue 8 (16th November 2016) - Saqib, Shahab E.; Ahmad, Mokbul Morshed; Panezai, Sanaullah
ABSTRACT: This article reports on a study that aimed to investigate the differences in access to, and utilisation of, agricultural credit among subsistence farmers in Pakistan. Primary data were collected from 87 randomly selected subsistence farmers. Results show that subsistence farmers with more land had greater access and utilisation, and that education, experience, type of farmer, and landholding size were significant factors influencing access to credit. As subsistence farmers with the least land were the most disadvantaged, there is a need for revamping the credit policy to protect their interests. Moreover, simplifying the existing complex procedures involved in securing agricultural credit is highly recommended.